Les acteurs de l'innovation et l'entreprise - Soussi, Sid-Ahmed (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "Les acteurs de l'innovation et l'entreprise," edited by Caroline Lanciano, Marc Maurice, Jean-Jacques Silvestre and Hiroatsu Nohara.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Innovation in business; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z